2019
DOI: 10.21595/jve.2018.18943
|View full text |Cite
|
Sign up to set email alerts
|

Effect of suction chamber baffles on pressure fluctuations in a low specific speed centrifugal pump

Abstract: In order to study the effect of suction chamber baffles on hydraulic performance and unsteady characteristics in a low specific speed centrifugal pump, a model pump was design with enlarging flow mothed and four schemes of suction baffle, including no baffle (scheme 0), only one baffle in the suction (scheme 1), two baffles (scheme 2) and three baffles in the suction (scheme 3), were considered. Commercial code FLUENT was applied to simulate the flow of the pump. RNG-turbulence model was adopted to handle with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The head and efficiency of the pump were increased when the baffle plate was installed at 36 °in the clock-wise direction. (Luo et al, 2019) studied three baffle plate configurations in a low specific speed centrifugal pump and found that baffle plates helped in decreasing the pressure pulsation amplitude in the volute. (Lin et al, 2020) studied the effect of an inlet guide vane installed at the inlet of a centrifugal pump and found to reduce the hydraulic losses and improve the hydraulic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The head and efficiency of the pump were increased when the baffle plate was installed at 36 °in the clock-wise direction. (Luo et al, 2019) studied three baffle plate configurations in a low specific speed centrifugal pump and found that baffle plates helped in decreasing the pressure pulsation amplitude in the volute. (Lin et al, 2020) studied the effect of an inlet guide vane installed at the inlet of a centrifugal pump and found to reduce the hydraulic losses and improve the hydraulic performance.…”
Section: Introductionmentioning
confidence: 99%